2018
DOI: 10.1021/jacs.7b10980
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Beneath the Surface: Origin of the Observed Enantioselective Adsorption on PdGa(111)

Abstract: We unravel the origin of the recently observed striking enantioselectivity of the PdGa(111) surface with respect to the adsorption of a small organic molecule, 9-ethynylphenanthrene, using first-principles calculations. It turns out that the key ingredient to understand the experimental evidence is the appropriate description of van der Waals interactions beyond the widely employed atomic pairwise approximation. A recently developed van der Waals-inclusive density functional method, which encompasses dielectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…This is about 1% of the reactant adsorption energy and most probably beyond the precision of the DFT calculations. [ 47 ] Therefore, DFT calculations on A:Pd 3 remain nonconclusive on the origin of the experimentally observed selectivity toward the S enantiomer. Consequently, we find that although DFT successfully predicts the correct adsorption configurations of the initial and final state, the accuracy is insufficient to capture the origin of the experimentally observed highly asymmetric halogen elimination.…”
Section: Resultsmentioning
confidence: 99%
“…This is about 1% of the reactant adsorption energy and most probably beyond the precision of the DFT calculations. [ 47 ] Therefore, DFT calculations on A:Pd 3 remain nonconclusive on the origin of the experimentally observed selectivity toward the S enantiomer. Consequently, we find that although DFT successfully predicts the correct adsorption configurations of the initial and final state, the accuracy is insufficient to capture the origin of the experimentally observed highly asymmetric halogen elimination.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the ensemble effect, the temperature evolution of the enantiomeric excess of 9‐EP structures and reaction products on PdGa{111}Pd 3 are in stark contrast to those on PdGa{111}Pd 1 . Specifically, whereas on PdGa{111}Pd 3 , 9‐EP monomers occur in a racemic mixture at 300 K, they appear with an enantiomeric excess of 96 % on PdGa{111}Pd 1 due to a lower energy barrier for the conversion between R and S monomers and the enantiospecific van der Waals interaction with the substrate's second layer Ga trimer . At elevated temperatures, however, all 9‐EP molecules form stable dimers on PdGa{111}{Pd 1 without enantioselectivity, whereas dimers on PdGa{111}Pd 3 are metastable and primarily intermediates for the homochiral and virtually enantiopure trimerization.…”
Section: Figurementioning
confidence: 99%
“…[25] Specifically, whereas on PdGa{111}Pd 3 , 9-EP monomers occur in a racemic mixture at 300 K, they appear with an enantiomeric excess of 96 % on PdGa{111}Pd 1 due to a lower energy barrier for the conversion between R and S monomers and the enantiospecific van der Waals interaction with the substrates second layer Ga trimer. [32] At elevated temperatures, however, all 9-EP molecules form stable dimers on PdGa{111}{Pd 1 without enantioselectivity, whereas dimers on PdGa{111}Pd 3 are metastable and primarily intermediates for the homochiral and virtually enantiopure trimerization. The obvious disparities in reaction pathway, kinetics, and enantioselectivity for the two structurally different PdGa{111} surfaces underline the significance of the ensemble effect and the need for an understanding of molecule-substrate interaction at atomic scales.…”
mentioning
confidence: 99%
“…Step–kink metal surfaces made by the transition and noble metals have been proposed for performing enantiospecificity. The enantiospecificity of the step–kink metal surface is reflected from the adsorption energy difference of enantiomers on metal surfaces. Step–kink metal surfaces can provide at least three configuration-dependent points for chemisorbing the enantiomers; this enhances their enantiospecificity significantly. Many studies have focused on the interaction of chiral molecules with stepped metal surfaces. ,, It has been shown that different α-amino acids have their own preferred chiral step–kink surface. For example, there is a significant adsorption energy difference when racemic aspartic acids are exposed to the Cu(3 1 17) surfaces, while a negligible adsorption energy difference was obtained when enantiomers of alanine were exposed to the same surface. ,,, Similarly, Cu(643) was found to efficiently separate enantiomers of 3-methylcyclohexanone, while Cu(531) was found to be the most efficient chiral separator for serine molecules. , Based on these observations, it is natural to ask whether there exists a universal step–kink surface, which has large enantiospecificity for various α-amino acids.…”
Section: Introductionmentioning
confidence: 99%